2013
DOI: 10.1155/2013/258029
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Prognostic Values of Serum TNF-αin Comparison to SOFA Score Monitoring in Critically Ill Patients

Abstract: Background. The use of inflammatory markers to follow up critically ill patients is controversial. The short time frame, the need for frequent and serial measurement of biomarkers, the presence of soluble receptor and their relatively high cost are the major drawbacks. Our study's objective is to compare the prognostic values of serum TNF-α and SOFA score monitoring in critically ill patients. Patients and Methods. A total of ninety patients were included in the study. Forty-five patients developed septic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…This C-index was superior to the C-indices of APACHE II (0.72) and SOFA scores (0.68), the golden standards in evaluating the sepsis severity. The SOFA score is included in the new definition of sepsis (Sepsis-3) 18 , and previous studies demonstrated that SOFA score is a good indicator of prognosis in ICU-admitted critically ill patients, especially those with severe sepsis 19 21 . Conversely, Liu et al reported in their meta-analysis that PCT was associated with mortality in septic patients and can moderately predict sepsis mortality 6 .…”
Section: Discussionmentioning
confidence: 99%
“…This C-index was superior to the C-indices of APACHE II (0.72) and SOFA scores (0.68), the golden standards in evaluating the sepsis severity. The SOFA score is included in the new definition of sepsis (Sepsis-3) 18 , and previous studies demonstrated that SOFA score is a good indicator of prognosis in ICU-admitted critically ill patients, especially those with severe sepsis 19 21 . Conversely, Liu et al reported in their meta-analysis that PCT was associated with mortality in septic patients and can moderately predict sepsis mortality 6 .…”
Section: Discussionmentioning
confidence: 99%
“…This study, however, studied dogs at admission to an intensive care unit, regardless of the presenting signs and previous history, and can therefore not be easily compared with this cohort of emergency patients with SIRS. The role of TNF‐α as an early mediator of the acute phase response with rapid downregulation makes it a poor diagnostic and prognostic tool in human critical care patients as well …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, during the first postoperative week, C group of patients showed a greater exposure to TNF- α and IL-8 with respect to the other 2 groups. TNF- α is known to be involved in systemic inflammatory response syndrome (SIRS), which usually precedes MOFS in several ill patients [ 14 , 15 ], while IL-8 is a specific monocyte attracting chemokines that modulates monocyte activation, an important condition in organ damage and haemostatic complications [ 16 ]. These data suggest that, immediately after MCS intervention, the extent of inflammatory response related mainly to TNF- α and IL-8 signals could influence the development and degree of MOFS severity, contributing to subsequent clinical evolution of ESHF patients.…”
Section: Discussionmentioning
confidence: 99%